A critical assessment of policy coordination in the Comprehensive Rural Development Programme: the case of Riemvasmaak - Maré, Annelie (Department of Political Studies, 2016)
Rural development has been a part of South Africa's policy agenda since the country's transition to democracy, but it has enjoyed new prominence since the ANC's policy conference at Polokwane in 2007 (ANC, 2008). This renewed interest in rural development as a policy priority culminated in the establishment of the new Department of Rural Development and Land Reform and the adoption of its flagship strategy, the Comprehensive Rural Development Programme (CRDP), in 2009. Even in its earliest incarnations, rural development was classified as a crosscutting policy problem beyond the scope of a single South African government department, therefore requiring horizontal coordination across sectors like land reform and agriculture, as well as vertical coordination with provincial departments serving concurrent functions. On the vertical plane, local government is also considered to be vital not only in identifying the needs of communities, but in their contributions to integrated planning processes. This study aims to examine the policy coordination mechanisms of the CRDP, including the new lead department tasked with its implementation, since the crosscutting nature of the policy problem necessitates such a wide variety of stakeholders coming together and taking a coordinated approach. The dissertation will focus on the town of Riemvasmaak in the Northern Cape as a case study, following a site visit and a series of semi-structured interviews conducted with officials from different spheres of government involved in the implementation of the new programme. The findings suggest that, despite the benefits of having a new national department, political support and financial resources at its disposal, policy coordination in the CRDP is not functioning as it should. The line between rural development and agriculture's mandates are becoming blurred, risking duplication between the two departments, while the CRDP's own chosen mechanism at grassroots, the Council of Stakeholders, seems to be duplicating existing Integrated Development Planning (IDP) processes at local government level. The findings also suggest that none of the chosen mechanisms proved adequate for resolving or overcoming conflict and other complexities hampering coordination at community level.